Respuesta :

10. y: -5x+y= -3--> *3 = -15x+3y= -9 ---> -37y= 111
3x-8y= 24--> *5 = 15x+40y= 120          /-37   /-37    y= -3

10. x: 
-5x+y= -3--> *8 = -40x+8y= -24 ---> -37x= 0
3x-8y=24--> *1 = 3x-8y= -24          /-37   /-37    x= 0

11. y: x
+3y=1--> *3 = 3x+9y= 3 ---> 6y= -12
-3x-3y=-15--> *1 = -3x-3y= -15          /6   /6    y= -2

11. x: x+3y=1--> *1 = x+3y= 1 ---> -2x= -14
-3x-3y=-15--> *1 = -3x-3y= -15          /-2   /-2    x= 7

12. y: -3x-8y=20 --> *-5 = 15x+40y= -100 ---> 43y= -43
-5x+y=19 --> *3 = -15x+3y= 57 --->                 /43    /43    y= -1

12. x: -3x-8y=20 --> *1 = -3x-8y= 20 ---> -43x= 172
-5x+y=19 --> *8 = -40x+8y= 152 --->                 /-43    /-43    y= -4